2010
DOI: 10.1111/j.1467-9507.2009.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Forms and Functions of Aggression in Adolescent Friendship Selection and Influence: A Longitudinal Social Network Analysis

Abstract: Aggressive children are known to have friends. However, less is known about the impact of aggression on friendship development and how this can differ for overt and relational (i.e., the forms) and instrumental and reactive (i.e., the functions) aggression. This longitudinal study utilized the forms and functions perspective on aggression to assess social selection and influence in adolescents' (N = 337, 12-14 years) friendship networks. Instrumentally and relationally aggressive peers became mutual friends wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 52 publications
(87 reference statements)
8
107
0
6
Order By: Relevance
“…Coalitions can occur opportunistically on a case-by-case basis (e.g., Bissonnette, 2009;Smith et al, 2010), or they can be observed frequently among the same partners as part of an enduring, long-term relationship (e.g., de Waal, 1982;Packer & Pusey, 1982;Smuts, 1985;Goodall, 1986;Noë, 1986b;Caro & Collins, 1987;Connor et al, 1992Connor et al, , 2001Feh, 1999;Boesch & BoeschAchermann, 2000;Boinski et al, 2005;Schülke et al, 2010). One individual may establish year-long, stable alliances with one or a few partners and also participate in opportunistic coalitions with other group members in which loyalties change regularly (Riss & Goodall, 1977;de Waal, 1982;Goodall, 1986;Noë, 1990;Uehara et al, 1994;Connor et al, 2000;Sijtsema et al, 2010). For example, Nishida (1983) and de Waal (1984) have argued that male chimpanzees intervene opportunistically in 'political' conflicts and may turn against former allies when it is beneficial to do so.…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
“…Coalitions can occur opportunistically on a case-by-case basis (e.g., Bissonnette, 2009;Smith et al, 2010), or they can be observed frequently among the same partners as part of an enduring, long-term relationship (e.g., de Waal, 1982;Packer & Pusey, 1982;Smuts, 1985;Goodall, 1986;Noë, 1986b;Caro & Collins, 1987;Connor et al, 1992Connor et al, , 2001Feh, 1999;Boesch & BoeschAchermann, 2000;Boinski et al, 2005;Schülke et al, 2010). One individual may establish year-long, stable alliances with one or a few partners and also participate in opportunistic coalitions with other group members in which loyalties change regularly (Riss & Goodall, 1977;de Waal, 1982;Goodall, 1986;Noë, 1990;Uehara et al, 1994;Connor et al, 2000;Sijtsema et al, 2010). For example, Nishida (1983) and de Waal (1984) have argued that male chimpanzees intervene opportunistically in 'political' conflicts and may turn against former allies when it is beneficial to do so.…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
“…Girls were also more likely to be victims (from both boys and girls), and the victimization seems to spread through groups of friends (Faris and Felmlee 2014). Similarly, social network analysis has revealed that adolescents select friends based on similar levels of instrumental aggression (Sijtsema et al 2010). …”
Section: Bullying and The Peer Contextmentioning
confidence: 99%
“…In addition, girls are more likely to tell a teacher, whereas boys are more likely to ignore bullying (Baldry 2005;Rigby and Johnson 2005;Rolider and Ochayon 2005). More recent research indicates that girls are more likely to use indirect interventions whereas boys use more direct (Sijtsema et al 2010). It is likely that the defending response is related to the extent to which it will be viewed favorably and if the person does not fear victimization as a result (Meter and Card 2015).…”
Section: Latané and Darley's (1970) Bystander Intervention Model: Appmentioning
confidence: 99%
“…In schools, students have been found to influence each other's deviant behavior, aggression, or academic achievement (Wentzel, Barry, and Caldwell 2004;Steglich et al 2006;Sijtsema et al 2010;Lomi et al 2011;Light et al 2013). Moreover (without suggesting causal inference), general prejudice against minorities is also found to be shared with friends in classrooms (Váradi 2014).…”
Section: General Peer Influence and Friendship Influencementioning
confidence: 99%